2015
DOI: 10.1155/2015/801709
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Casual In-Clinic Blood Pressure Measurements to Standardized Guideline-Concordant Measurements in Severely Obese Individuals

Abstract: Background/Objectives. The objective of this study was to compare casual BP taken in a bariatric clinic to standardized guideline-concordant BP. Subjects/Methods. A cross sectional analysis was performed using baseline data from a weight management trial. Patients were recruited from a Canadian bariatric care program. Standardized BP was performed using a Watch BP oscillometric device. Casual in-clinic BP single readings, taken using a Welch Allyn oscillometric device, were chart-abstracted. Paired t-tests, Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Similar to this study, a previous Canadian study that compared casual in-clinic BP measurements to standardised BP measurements among severely obese patients in a bariatric clinic also found that casual in-clinic BP measurements were, on average, lower than standardised measurements. 18 Unlike the index study and the Canadian study, the previous studies on this topic, however, reported contrary conclusions; that is, usual-care BP measurements were higher than standardised measurements. 7,8,19,20 A South African study showed that the mean usual-care SBP and DBP were significantly higher than mean guidelineconcordant SBP and DBP by 10.7 mmHg and 3 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similar to this study, a previous Canadian study that compared casual in-clinic BP measurements to standardised BP measurements among severely obese patients in a bariatric clinic also found that casual in-clinic BP measurements were, on average, lower than standardised measurements. 18 Unlike the index study and the Canadian study, the previous studies on this topic, however, reported contrary conclusions; that is, usual-care BP measurements were higher than standardised measurements. 7,8,19,20 A South African study showed that the mean usual-care SBP and DBP were significantly higher than mean guidelineconcordant SBP and DBP by 10.7 mmHg and 3 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…The potential explanation for the observed difference in findings between the index study or Canadian study and previous studies 7,8,19,20 concerning the variation between usual-care and guideline-concordant BP can be ascribed to the different BP measurement protocol that was used in the guideline-concordant measurement protocol. While our study and the Canadian study 18 employed dual-arm BP measurement and used the arm with higher reading for the guideline-concordant BP, the previous studies 7,8,19,20 used the readings from a single arm as the guideline-concordant value. The use of a single arm for measuring guideline-concordant BP in the previous studies 7,8,19,20 is not in conformity with BP measurement guidelines that stipulated dual-arm BP measurements at the initial visit and subsequent measurement of BP in the arm with higher reading.…”
Section: Discussionmentioning
confidence: 99%
“…Details are available elsewhere (NCT 01860131) [2,7]. The University of Alberta Research Ethics Board approved the study protocol and informed consent was obtained from all participants.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Much of the increase in cardiovascular risk found in severe obesity is mediated through elevated blood pressure (BP), which is present in about two-thirds of severely obese patients [2].…”
Section: Introductionmentioning
confidence: 99%